How AIS Addresses Adaptability in IDS - Zainal, Anazida; Maarof, Mohd. Aizaini; Shamsuddin, Siti Mariyam (2005)
Immune system is essential to human body as it protects our bodies from pathogens in an orchestrated manner. The attractive feature of this system is its ability to detect and fight against various kinds of pathogens. The adaptive process to match the shape of epitopes and gene library evolution manifest that the system is adaptive. Since body protection against pathogens is analogous to network protection against intruders, this has led many researchers to embark on the Intrusion Detection research deploying the Immune System approach. The discussion in this paper focuses on the aspects of adaptability of Immune System and how it is implemented in IDS. Three major works representing three major evolutionary processes in human immune system were chosen to be reviewed.